Influence of Actors on the Development of the Extractive Industry Sector in Nigeria - Fom, John Baling; Sha , Dung Pam; Umoh, Nanji R. (Kashere Journal of Politics and International Relations, 2025)
The Nigeria's extractive industry is governed by a complex network of actors, each with varying degrees of power and influence. This study examines the key stakeholders and the attributing factors that impact resource governance in the extractive sector. Government agencies, multinational corporations, local communities, civil society organizations, and international business entities play significant roles in shaping policies and regulations within the industry. This paper employs a qualitative approach to data collection and examines the interplay between these actors to define their level of influence in different spheres of interest within the extractive industry in Nigeria. The study discovered that while the Nigerian government has considerable authority through regulatory frameworks and licensing agreements, corruption and politically motivated conditions often hinder its effectiveness in enforcing these regulations. Conversely, private entities also have dominant influence on the market which include, price mechanism and control over demand. Nigeria's abundant natural resources attract multinational corporations and exert considerable influence through investment capacity and technological expertise. However, there is no balance between actor’s engagements as it affects employment creation and value addition process. Local communities affected by environmental degradation and socio-economic inequalities, increasingly lack greater participation and benefits from resource extraction activities. Despite challenges in reconciling competing interests and power dynamics, inclusive and participatory approaches are needed for effective resource governance in Nigeria's extractive industry. The study recommends that Civil Society Organizations and international bodies should progressively advocate for transparency, accountability, and sustainable practices, acting as watchdogs to pressure government and corporate actors to comply with best practices.